The Eoplacognathus suecicus Zone (Conodonta) in the Central Precordillera, Argentina - Heredia, Susana (2010)
The Middle Ordovician carbonate Las Aguaditas Formation was sampled for conodonts at the Las Chacritas Creek, Sierra de La Trampa, Central Precordillera. The middle Darriwilian index conodonts Eoplacognathus pseudoplanus Viira and Eoplacognathus suecicus Bergström define the biostratigraphy of the lower Member of the Las Aguaditas Formation. The biostratigraphic scheme includes the Pygodus lunensis and Pygodus anitae Subzones of the E. suecicus Zone. Using this biostratigraphic scheme, it is possible to correlate with Baltica and south-central China.